ANALISI FINTECH TERHADAP PERKEMBANGAN PRODUK PERBANKAN SYARIAH DI BPRS ARTHA AMANAH UMMAT UNGARAN KABUPATEN SEMARANG - Anggraeni Tri Lestari; Andhi Supriyadi (Media Bina Ilmiah, 2025)
The financial system based on technology is called Fintech and builds new products, services, technologies, and business models. This affects the stability of the financial system, smoothness, security, and speed of payments. The presence of fintech in the banking industry benefits both banks and customers. In practice, fintech can streamline the process of handling various tasks so that they are faster and more efficient. This study aims to determine how Fintech affects product development at BPRS Artha Amanah Ummat Ungaran, Semarang Regency. This field study has qualitative descriptive characteristics. Primary data was obtained from interviews, and secondary data was obtained from literature studies or documentation to complement the primary data. The study shows that the presence of fintech affects the progress of Islamic banking products. Customers really like some good financial technology products; one of which is a paperless online account, which reduces paper use because all transaction models are now internet-based.